Anti-Muslim racism on trial: Muslims, the Swedish judiciary and the possibility of justice - Kolankiewicz, Marta (Routledge research in race and ethnicity, 2019)
Introduction -- Anti-Muslim racism : scales and contexts -- Meeting with the court documents : methodological reflections -- Making racism a crime -- On the politics and poetics of hate-crime statistics -- In search of a racist subject -- Hate speech, linguistic injury and language in court -- On judging and responsibility -- Conclusions.